Mimicry Marketing Strategy on Marketing Performance of Small and Medium Enterprise - Suliyanto S (Faculty of Economics and Business, University of Pasundan, 2015)
The background of this research is the failure of the marketing orientation concept and the unprepared consumers to accept the societal marketing concept. There needs orientation phase that are between the marketing orientation phase and societal marketing phase. The orientation phase is Adaptive Marketing Orientation (AMO).One of the applications of adaptive marketing orientation is Mimicry Marketing Strategy (MMS). The purpose of this study is to analyze the effect of MMS to competitors, MMS to consumers, MMS to suppliers, MMS to intermediarieson the quality of relationship with partners and innovation as well as to analyze the influence of the quality of relationship with partners and innovation to the marketing performance. Samples are 100 SMEs in Banyumas; data analysis tool used is Path Analysis. The results of this study found that the effect of MMS to consumers and MMS to competitors have positive effect on innovation and the quality of relationship with partners, while MMS to suppliers, and MMS to intermediarie shave no positive effect on innovation and the quality of relationship with partners, and the quality of relationship with partners and innovations have positive effect toward marketing performance.